Development of models for segregation of infrastructure project management elements using a mono-template in safety-oriented management - Kobylkin, Dmytro; Zachko, Oleh; Korogod, Nataliia; Tymchenko, Daria (Eastern-European Journal of Enterprise Technologies, 2020)
A comprehensive study of the process of decomposition and segregation of infrastructure project management elements using a mono-template under the influence of changes and safety-oriented management was carried out. The use of project, program and portfolio management tools made it possible to generalize the process of structural decomposition of infrastructure projects and features of segregation of management elements using a mono-template and provisions of safety-oriented management. This is important because of the peculiarities of the formation and planning of infrastructure projects: content, structure requirements and values, among which safety is the key. Thus, a conceptual schematic model of a mono-template in safety-oriented management is developed, which includes three blocks of project management. This made it possible to improve the planning process of infrastructure projects. The schematic model is developed and the application of the filter system of elements and parameters of infrastructure project management in safety-oriented management is proposed. The system allows carrying out the process of segregation of the necessary elements and parameters of infrastructure project management with the use of a mono-template. The influence and consequences of application on the basis of project parameters are described. A formalized model of the segregation process of infrastructure project management elements and parameters at the level of a mono-template in safety-oriented management is presented. The process of transition of structurally decomposed management elements and parameters through the filter system is described. In the course of this process, the project factors of proactive management, internal project environment, changes and system resistance affect the formed structurally decomposed blocks of a mono-template. The models developed in the study complement the project management tools and provide an opportunity to carry out the process of planning infrastructure projects at a high-quality level